PENILAIAN UNJUK KERJA PT. X & PT. Y BERDASARKAN METODE BENCHMARKING - Kohar Sulistyadi; Yudhi Ismara (Universitas Sahid Surakarta, 2015)
Many ways to assess the performance of a company, in this case the shoe company needs to create value advantages for consumers, some of the factors that support for the achievement of the efficiency value, mimimasi costs, business competence, the demands of a dynamic market. to get a gap value of each company's performance on a benchmarking approach is needed. Benchmarking is a continuous process of measuring products, services and practices against the toughest competitors a recognized risk management. The purpose of this paper are : (1). Finding an effort to catch up with PT. Y should improve performance for changes and improvements, based on the destination map balance (parity goal) with the assumption that it takes three years to equalize with PT Y with the aim of: (a) the first six months of the formation of the team for the analysis of constraints, (b) testing the application of the second six-month evaluation, and (c) the periodic application; (2). Designing a proposal to replace the conventional purchase procedures; (3). Training for increased performance human resources; and (4). Evaluate the improvement of all activities with the benchmarking approach. The end result is to get the value of the performance of competitors, comparing the position of some elements between the two companies is based on: (a) technical quality, (b) speed of the material arrival time, (c) value reliability, and (d) evaluation of suppliers.